The Economic Factors Affecting the Agricultural Economic Structure of Laos - souksitthi, sisouphan; Siphanthong, Bounthavy; SIOUDOMPHAN, Soutthavone (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
The research on the Economic factors affecting the agricultural economic structure of Laos this time has brought the collected data to summarize, interpret, consider, select, and analyze the inferential statistics to find the parameter value of the regression equation using the Ordinary Least Square method of the economic factors affecting the agricultural economic structure of Laos through the Statistic program. The results of the research found: Changes in the agricultural economic structure of Lao PDR from 2006-2023. The GDP value of the agricultural sector of Lao PDR has a total value of 28,602.21 million US dollars, accounting for 17.92% of the GDP of Lao PDR. The year with the greatest increase is 2012, which increased from 1,190.62 million US dollars, equal to 58.59%. This is because in that year the government of the Lao PDR has taken measures and policies to stimulate the economy continuously so that various investment projects are implemented according to the plan, and the year in which the GDP value of the agricultural sector has decreased the most is the year 2022, which has decreased to 25.58% and decreased to only 1,360.18 million US dollars. In addition, the research results on the economic factors affecting the total agricultural production productivity of the Lao PDR also found that the value of foreign direct investment (FDI), the degree of openness of the country (TO), and the labor force ratio (LST) have a relationship in the same direction with the agricultural productivity of the Lao PDR (Agr) with a statistical significance of 0.05 and 0.10, respectively; the public sector expenditure (GE) and the inflation rate (Inf) are not statistically significant.